Germanium doping of cubic GaN grown by molecular beam epitaxy - Deppe, M.; Gerlach, J. W.; Shvarkov, S.; Rogalla, D.; Becker, H.-W.; Reuter, Dirk; As, Donat Josef (Journal of Applied Physics)

Divide and Compact - Stochastic Space Compaction for Faster-than-At-Speed Test - Sprenger, Alexander; Hellebrand, Sybille (Journal of Circuits, Systems and Computers)

Prototyping and Demonstrating 5G Verticals: The Smart Manufacturing Case - Peuster, Manuel; Schneider, Stefan Balthasar; Behnke, Daniel; Müller, Marcel; Bök, Patrick-Benjamin; Karl, Holger (5th IEEE International Conference on Network Softwarization (NetSoft 2019))
5G together with software defined networking (SDN) and network function virtualisation (NFV) will enable a wide variety of vertical use cases. One of them is the smart man- ufacturing case which utilises 5G networks to interconnect production machines, machine parks, and factory sites to enable new possibilities in terms of flexibility, automation, and novel applications (industry 4.0). However, the availability of realistic and practical proof-of-concepts for those smart manufacturing scenarios is still limited. This demo fills this gap by not only showing a real-world smart manufacturing application entirely implemented using NFV concepts, but also a lightweight prototyping framework that simplifies the realisation of vertical NFV proof-of-concepts. Dur- ing the demo, we show how an NFV-based smart manufacturing scenario can be specified, on-boarded, and instantiated before we demonstrate how the presented NFV services simplify machine data collection, aggregation, and analysis.

A flow handover protocol to support state migration in softwarized networks - Peuster, Manuel; Küttner, Hannes; Karl, Holger (International Journal of Network Management)
Softwarized networks are the key enabler for elastic, on-demand service deployments of virtualized network functions. They allow to dynamically steer traffic through the network when new network functions are instantiated, or old ones are terminated. These scenarios become in particular challenging when stateful functions are involved, necessitating state management solutions to migrate state between the functions. The problem with existing solutions is that they typically embrace state migration and flow rerouting jointly, imposing a huge set of requirements on the on-boarded virtualized network functions (VNFs), eg, solution-specific state management interfaces. To change this, we introduce the seamless handover protocol (SHarP). An easy-to-use, loss-less, and order-preserving flow rerouting mechanism that is not fixed to a single state management approach. Using SHarP, VNF vendors are empowered to implement or use the state management solution of their choice. SHarP supports these solutions with additional information when flows are migrated. In this paper, we present SHarP's design, its open source prototype implementation, and show how SHarP significantly reduces the buffer usage at a central (SDN) controller, which is a typical bottleneck in state-of-the-art solutions. Our experiments show that SHarP uses a constant amount of controller buffer, irrespective of the time taken to migrate the VNF state.

Nonlinear optics in all-dielectric nanoantennas and metasurfaces: a review - Sain, Basudeb; Meier, Cedrik; Zentgraf, Thomas (Advanced Photonics)
Free from phase-matching constraints, plasmonic metasurfaces have contributed significantly to the control of optical nonlinearity and enhancement of nonlinear generation efficiency by engineering subwavelength meta-atoms. However, high dissipative losses and inevitable thermal heating limit their applicability in nonlinear nanophotonics. All-dielectric metasurfaces, supporting both electric and magnetic Mie-type resonances in their nanostructures, have appeared as a promising alternative to nonlinear plasmonics. High-index dielectric nanostructures, allowing additional magnetic resonances, can induce magnetic nonlinear effects, which, along with electric nonlinearities, increase the nonlinear conversion efficiency. In addition, low dissipative losses and high damage thresholds provide an extra degree of freedom for operating at high pump intensities, resulting in a considerable enhancement of the nonlinear processes. We discuss the current state of the art in the intensely developing area of all-dielectric nonlinear nanostructures and metasurfaces, including the role of Mie modes, Fano resonances, and anapole moments for harmonic generation, wave mixing, and ultrafast optical switching. Furthermore, we review the recent progress in the nonlinear phase and wavefront control using all-dielectric metasurfaces. We discuss techniques to realize all-dielectric metasurfaces for multifunctional applications and generation of second-order nonlinear processes from complementary metal–oxide–semiconductor-compatible materials.

Ideenbewertung durch die Crowd - Ein klassifizierender Literaturüberblick - Groh, Andreas

Detection and Resolution of Data-Flow Differences in Business Process Models - Jovanovikj, Ivan; Yigitbas, Enes; Gerth, Christian; Sauer, Stefan; Engels, Gregor (Information Systems Engineering in Responsible Information Systems - CAiSE Forum 2019, Rome, Italy, June 3-7, 2019, Proceedings)

Modular Construction of Context-Specific Test Case Migration Methods - Jovanovikj, Ivan; Yigitbas, Enes; Grieger, Marvin; Sauer, Stefan; Engels, Gregor (Proceedings of the 7th International Conference on Model-Driven Engineering and Software Development - Volume 1: MODELSWARD,)

# Fail - Ein Literaturüberblick über Online-Bewertungen zu Produkt- und Dienstleistungsfehlern - Fath, Jerome Louis

Activate software-based business model development tools: An exploratory study - Szopinski, Daniel (3rd Business Model Conference)

The long tail of taxonomy evaluation criteria: A structured overview - Szopinski, Daniel; Schoormann, T.; Kundisch, Dennis (Proceedings of the 14th International Conference on Design Science Research in Information Systems and Technology (DESRIST))

Consistent Runtime Adaptation of User Interfaces - Anjorin, Anthony; Yigitbas, Enes; Kaindl, Hermann (Proceedings of the 8th International Workshop on Bidirectional Transformations (Bx 2019))

Scheduling on (Un-)Related Machines with Setup Times - Jansen, Klaus; Maack, Marten; Mäcker, Alexander (Proceedings of the 33rd IEEE International Parallel and Distributed Processing Symposium (IPDPS))

Towards Automated Machine Learning for Multi-Label Classification - Wever, Marcel Dominik; Mohr, Felix; Hüllermeier, Eyke; Hetzer, Alexander

Distributed Computation in Node-Capacitated Networks - Augustine, John; Ghaffari, Mohsen; Gmyr, Robert; Hinnenthal, Kristian; Kuhn, Fabian; Li, Jason; Scheideler, Christian (Proceedings of the 31st ACM Symposium on Parallelism in Algorithms and Architectures)

Light scattering by 3-Foci convex and concave particles in the geometrical optics approximation - Stankevich, Dmitriy; Hradyska, Larissa; Shkuratov, Yuriy; Grynko, Yevgen; Videen, Gorden; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
We consider light scattering from a new type of model particle whose shape is represented in the form of a generalized ellipsoid having N foci, where N is greater than two. Such particles can be convex as well as concave. We use the geometrical optics approximation to study the light scattering from 3-foci particles. Non-zero elements of the scattering matrix are calculated for ensembles of randomly oriented independent transparent particles, m = n + i0. Several internal reflection orders are considered separately. It was found that the transmission-transmission (TT) and transmission-reflectance-transmission (TRT) components dominate in the formation of intensity of scattered light at large and small phase angles, respectively. We found a significant role of the total internal reflections of the TRT in the middle portion of the phase angle range. The main factors in the formation of positive linear polarization are the R and TRT component. The TT component is responsible for the formation of negative polarization branch at large phase angles.
Keywords: tet_topic_scattering

Credence Goods Markets with Fair and Opportunistic Experts - Heinzel, Joachim Maria Josef
We analyze a credence goods market adapted to a health care market with regulated prices, where physicians are heterogeneous regarding their fairness concerns. The opportunistic physicians only consider monetary incentives while the fair physicians, in addition to a monetary payoff, gain an non-monetary utility from being honest towards patients. We investigate how this heterogeneity affects the physicians’ equilibrium level of overcharging and the patients’ search for second opinions (which determines overall welfare). The impact of the heterogeneity on the fraud level is ambiguous and depends on several factors such as the size of the fairness utility, the share of fair physicians, the search level and the initial fraud level. Introducing heterogeneity does not affect the fraud or the search level when the share of fair physicians is small. However, when social welfare is not at its maximum, social welfare always increases if we introduce a sufficiently large share of fair physicians.
Keywords: credence goods; heterogeneous experts; fairness; overcharging

Towards Model-based Development of Context-aware Augmented Reality Applications - Yigitbas, Enes; Jovanovikj, Ivan; Sauer, Stefan; Engels, Gregor (Softwaretechnik-Trends, Proceedings of the 21st Workshop Software-Reengineering & Evolution (WSRE) & 10th Workshop Design for Future (DFF))

Attracting attention from peers: Excitement in social trading - Pelster, Matthias; Breitmayer, Bastian (Journal of Economic Behavior & Organization)

Computing by Programmable Particles - Daymude, Joshua J.; Hinnenthal, Kristian; Richa, Andréa W.; Scheideler, Christian (Distributed Computing by Mobile Entities, Current Research in Moving and Computing.)